Distribution of Diarrhetic Shellfish Toxins in Mussels, Scallops, and Ascidian - Matsushima, Ryoji (Food Saf (Tokyo), 2018)
Diarrhetic shellfish toxins (DST) are a group of phycotoxins that include Okadaic acid (OA) and structurally related toxins. In Japan, the regulatory limit of DST in shellfish for human consumption is a total OA equivalent of 0.16 mg per kg of edible tissue. Distribution and individual differences of DST in scallops collected in Aomori Prefecture were investigated. Fourteen to 20 individual scallops were divided into hepatopancreas, gonads, mantles, gills, adductor muscles, and the concentrations of diarrhetic shellfish poisoning (DSP) in each tissue were quantified by LC/MS/MS after hydrolysis. The dominant toxin in the scallops was Dinophysis toxin 1 (DTX1). More than 97% of the observed DTX1 in the scallop tissue was detected in the hepatopancreas and the average level of DTX1 was higher in mussels than the scallops. The number of individual scallops or mussels required to correctly reflect the DTX1 content of a sample group was estimated by resampling. In scallops, using 10 individuals fell within ± 20% of 30 individual’s average with a probability of 99.8%. On the other hand, in the blue mussel, an average of 19 individuals fell within ± 20% of 30 individual’s average with 98% probability. In addition, the analysis of the DST in ascidians collected from Miyagi Prefecture was carried out. The muscles, gills, hepatopancreas and intestines were analyzed. High concentration of both DTX1 and OA were detected in the hepatopancreas after hydrolysis. Low levels of DST were detected from other tissues, indicating that DST are primarily accumulated in the hepatopancreas in the ascidians.